Investigating the Relationship between Leadership Styles and Organizational Performance in Higher Education - Tembo, Chipozya; Tabalasa, Karen; Muleya, Franco (African Journal of Education and Practice, 2024)
Purpose: This research aimed to uncover the role of leadership style in the performance of higher education institutions (H.E.I.s) in Zambia. Methodology: The study utilized a positivist philosophy and collected data randomly and using a census from various University leadership cross sectionally. Using ninety-seven self-administered questionnaires where sixty-nine questionnaires were collected representing a response rate of 71.11%. The data was analyzed using descriptive and inferential statistics to explain the Performance of H.E.I.s and uncover the relationship between performance and leadership style. Findings: The most utilized leadership styles in H.E.I.s are transactional and transformational. Laissez-faire leadership was rarely used, with a higher utility in public universities where this mode of leadership was significantly correlated with research. The order of performance in descending order in H.E.I.s is teaching, size, prestige, impact, internationalization, and research. As mentioned earlier, inspirational motivation and contingent reward had weak to moderate significant positive correlation with performance. Unique Contribution to Theory, Practice and Policy: The research only focused on leadership style as a predictor of performance. Additionally, the research cannot be generalized as few Universities, both private and public, were part of the target population. The leaders in public and private universities should focus on inspirational motivation and contingent reward aspects of transactional and transformational leadership to improve underperforming performance areas, except for prestige in improving performance. This will increase the number of enrollment of students.